2016
DOI: 10.5897/ajmr2015.7781
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of probiotic potential of five lactic acid bacteria and their antimicrobial activity against some enteric and food-borne pathogens

Abstract: Lactic acid bacteria (LAB) present many important properties in food manufacturing, such as improvement of physical characteristics and the production of lactic acid that aids in the increase of the shelf life of food products. Also, LAB can suppress growth of pathogens, control of serum cholesterol level, modulate immune system, and improve lactose digestion. Five standard (Lactobacillus paracasei, Lactobacillus helveticus, Lactobacillus fermentum, Bifidobacterium longum and Lactococcus lactis) lactic acid ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Lactic acid bacteria (LAB) have proven efficacies for food preservation and enhance the nutritive quality of a variety of fermented food products (Gad et al, 2016). Primarily, the LAB exert their antimicrobial effects by producing lactic acid, which increases the acidity of their environment, thereby resulting in the loss of the viabilities of pathogenic bacteria (Ammor et al, 2006; Gad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactic acid bacteria (LAB) have proven efficacies for food preservation and enhance the nutritive quality of a variety of fermented food products (Gad et al, 2016). Primarily, the LAB exert their antimicrobial effects by producing lactic acid, which increases the acidity of their environment, thereby resulting in the loss of the viabilities of pathogenic bacteria (Ammor et al, 2006; Gad et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Primarily, the LAB exert their antimicrobial effects by producing lactic acid, which increases the acidity of their environment, thereby resulting in the loss of the viabilities of pathogenic bacteria (Ammor et al, 2006; Gad et al, 2016). Low molecular weight compounds, such as, hydrogen peroxide, carbon dioxide, diacetyl (2,3-butanedione), and bacteriocins also contribute to antimicrobial effects of LAB (Ammor et al, 2006; Sankarankutty and Palav, 2016), as they substantially inhibit the growths of pathogenic bacteria in food system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Egypt, the highest antagonistic activity was observed for Lactobacillus paracasei and L. helveticus against the tested pathogens followed by L. fermentum, while Bifidobacterium longum and L. lactis subsp. lactis showed weak or no antibacterial activity against the tested strains (23).…”
Section: Discussionmentioning
confidence: 95%
“…Intestinal microorganisms are important in terms of regulating digestion and improving host performance through the fermentation of non-digestible polysaccharides, resulting in the production of beneficial volatile fatty acids (VFA), particularly butyrate [5,7]. Furthermore, the colonisation of the intestinal mucosa and lumen by commensal bacteria reduces the accessibility of pathogens to both nutrients and attachment sites [8,9]. Marine macroalgal derivatives have been considered as potential bioactive compounds in swine nutrition and in particular as a prebiotic that can favourably support the intestinal microbiome [4,10,11].…”
Section: Introductionmentioning
confidence: 99%